Time to Change: Temporal Shifts as Enablers of Organizational Change - Staudenmayer, Nancy; Tyre, Marcie; Perlow, Leslie (Organization Science, 2002)
In this paper, we integrate findings from three field studies of technology intensive organizations to explore the process through which change occurred. In each case, problems were well recognized but had become entrenched and had failed to generate change. Across the three sites, organizational change occurred only after some event altered the accustomed daily rhythms of work, and thus changed the way people experienced time. This finding suggests that temporal shifts—changes in a collective's experience of time—can help to facilitate organizational change. Specifically, we suggest that temporal shifts enable change in four ways: (1) by creating a trigger for change, (2) by providing resources needed for change, (3) by acting as a coordinating mechanism, and (4) by serving as a credible symbol of the need to change.